Implementation of Cartoon Learning Media in Islamic Religious Education Subjects at Rahmat Islamiyah Junior High School Medan - Hasrian Rudi Setiawan; Eka Cahyati Sitorus (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to describe the implementation of cartoon learning media in Islamic Religious Education subjects at Rahmat Islamiyah Junior High School Medan. The research employed a qualitative approach using a descriptive method. The research participants consisted of the principal, Islamic Religious Education teachers, and students. Data were collected through observation, interviews, and documentation. The findings revealed that the use of cartoon learning media in Islamic Religious Education significantly increased students’ attention, interest, and learning motivation. Cartoon media assisted teachers in presenting abstract concepts in a more concrete, engaging, and understandable manner. Furthermore, students became more active during the learning process and were able to retain the learning materials more effectively. Supporting factors included the availability of technological facilities and teachers’ creativity in developing instructional media, while inhibiting factors involved limited time and the varying abilities of teachers in designing attractive cartoon media. Therefore, cartoon learning media can serve as an innovative alternative to improve the quality of Islamic Religious Education learning at Rahmat Islamiyah Junior High School Medan.